2015
DOI: 10.1142/s0219525915500010
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Markets and Behavioral Finance: A Comprehensive Multifractional Model

Abstract: Real-world financial dynamics daily do challenge the credibility of the Efficient Market Hypothesis, the pillar of the whole martingale-based modern financial theory stating that at any time asset prices discount all past information. As a matter of fact, the empirical evidence accumulated so far indicates that current models cannot explain the complexity of financial market movements, to the extent that a strand of skeptical thought, the Behavioral Finance, has been booming. The question whether a model exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…SME owners who have a high level of literacy will have better financial behavior. These findings are consistent with the study of (Arifin, 2017;Bianchi et al, 2015;Kumar, Suresh;Watung, Christalita;N. Eunike, Josephine;Luinata, 2017;Lusardi et al, 2017;Sayinzoga et al, 2016;Strömbäck et al, 2017;Tang & Baker, 2016;Thi et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SME owners who have a high level of literacy will have better financial behavior. These findings are consistent with the study of (Arifin, 2017;Bianchi et al, 2015;Kumar, Suresh;Watung, Christalita;N. Eunike, Josephine;Luinata, 2017;Lusardi et al, 2017;Sayinzoga et al, 2016;Strömbäck et al, 2017;Tang & Baker, 2016;Thi et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…They show that inequalities in financial literacy are the main determinants of income disparity because they increase differences in wealth accumulation patterns. Bianchi, Pantanella, & Pianese (2015) found that financial literacy affects household portfolio selection and return rates. The same results are shown in the research of Kumar, Suresh, Watung, Christalita; N. Eunike, Josephine; Luinata (2017), who found evidence that financial literacy affected financial behavior.…”
Section: The Relationship Between Financial Literacy and Financial Be...mentioning
confidence: 99%
“…The research of Yu and Zheng (2015) shows, investors do not always adopt rational behaviour as the traditional finance theory assumed but make many irrational decisions based on individual cognitive and prejudices. In addition, the fact that the traditional model cannot explain the complexity of financial market movements makes the field of behavioural finance boom (Bianchi et al, 2015). Some authors even indicate the shift from behavioural finance to social finance, which studies the structure of social interactions, how financial ideas spread and evolve and how social processes affect financial outcomes (Hirshleifer, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This paper seeks to determine the dimensions underlying those variables observed in the construct of the capital structure, establishing systematic relations among the variables to assess cognitive behaviors and to establish their relationship to financial theory. Interpreting the theory of capital structure at a construct level 4 The concept of the WACC is commonly accepted but there are a number of different models and formulae that can be used to estimate this cost, for example, the "real WACC" and the "nominal WACC". The real WACC excludes inflation from the calculated return and is applied to a regulatory asset base that is indexed by inflation.…”
Section: Constructs In Human Behavior Researchmentioning
confidence: 99%